Innovation and creativity to foster a critical and systemic thinking: high-level ideas in initial teacher training (Foro de Educacion, 2015)
This work is in the framework of a training curriculum greening model applied in the initial teacher training of primary education. We analyze the functional characterization of high-level ideas that are the basis of this model. The research is considered as interpretative-descriptive one, with a methodology of qualitative analysis. The data collected are from 44 student productions (students of the 4th course of Primary Education Degree). From the analysis different profiles have been typified in the sequence of developmental stages of the model (at baseline, short term and long term changes). It also allowed us to characterize their reflection processes when starting from initial conditions determined perceptually by cognitive conflict (chaos, obstacles) or simple learning opportunities. In this sense, we note how initial chaotic situations (cognitive conflict) are strongly interrelated with long term justifications (changes in worldview and deeper reflections). This research opens the way to conceptualize the high-level ideas and their use in future learning processes, as well as to regulate the curriculum greening training model.